2019
DOI: 10.7717/peerj.6199
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine-induced alteration of murine gut microbial community structure: evidence for a microbial endocrinology-based mechanism of action responsible for fluoxetine-induced side effects

Abstract: BackgroundDepression and major depressive disorder affect 25% of the population. First line treatment utilizing selective serotonin reuptake inhibitors (SSRIs) have met with limited success due to well-recognized negative side effects which include weight gain or loss. This inability to control unwanted side effects often result in patients stopping their antidepressant medications. The mechanisms underlying the failure of SSRIs are incompletely understood.MethodsMale CF-1 mice (5 weeks of age, N = 10 per grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 45 publications
1
36
1
2
Order By: Relevance
“…This is consistent with the gut microbial composition in metabolic diseases revealed by many researchers [24]. The Muribaculum genus, previously classified as S24-7, is known to decrease in mice on high-fat diet and is associated with the regulation of body weight [25,26]. Moreover, Romboutsia, which is an obesity-related phylotype, is positively associated with lipid profile and lipogenesis in the liver [27].…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with the gut microbial composition in metabolic diseases revealed by many researchers [24]. The Muribaculum genus, previously classified as S24-7, is known to decrease in mice on high-fat diet and is associated with the regulation of body weight [25,26]. Moreover, Romboutsia, which is an obesity-related phylotype, is positively associated with lipid profile and lipogenesis in the liver [27].…”
Section: Discussionsupporting
confidence: 82%
“… Study Study design Highlighted findings FLX-treated vs vehicle-treated animals Corresponds to current results? Cussotto et al 2019 24 Male rats, 28 days of 10 mg/kg/day, in drinking water Alpha diversity: no significant difference Yes OTU abundance: depletion of Prevotella 7 and 9 No; we found increases in Prevotella Lyte et al 2019 25 Male mice, 29 days of 20 mg/kg/day, oral gavage Alpha diversity: no significant difference Yes OTU abundance: decrease in S24–7 ( Bacteroidales ) Potentially; we found decreases in several Bacteroidales OTUs Lukić et al 2019 26 Male mice, 21 days of 10 mg/kg/day, IP injections Alpha diversity: decrease No OTU abundance: decrease in Ruminococcus No Zhu et al 2019 27 Male rats, 21 days of 2 mg/kg/day, oral gavage, daily stress Alpha diversity: no significant difference Yes OTU abundance: Prevotellaceae Ga6A1 decreased, and Ruminoclostridium 6 and Ruminococcaceae NK4A214 increased Potentially; we found increases in Ruminococcus Fung et al 2019 28 Male and female mice, 7 days of 10 mg/kg/day, oral gavage OTU abundance: decrease in Turicibacter No (data not shown) Sun et al 2019 29 Male mice, 21 days of 12 mg/kg/day, oral gavage, daily stress Alpha diversity: no significant difference Yes …”
Section: Discussionmentioning
confidence: 68%
“… 16 , 22 , 23 Moreover, recent experiments showed that FLX alters the gut microbiota in rats, 24 , 27 and in mice. 25 , 26 , 28 , 29 Interestingly, the specific bacteria underlying this difference do not match between studies ( Table 1 ). Whereas we found significant increases in Prevotella and Ruminococcus relative abundance during pregnancy and lactation in FLX-treated rats, Cussotto et al report a complete depletion of some Prevotella OTUs in FLX-treated male rats, 24 and Lukić et al found many Ruminococcaceae OTUs to be lower in FLX- and escitalopram-treated mice relative to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, other evidence gathered from animal studies suggested that the antidepressants modulate the composition of the intestinal microbiota 9,[16][17][18] . Administration of TCA desipramine causes important side effects and results in a higher incidence of infections generating gingivitis and dysbiosis of oral microbiota 19 .…”
mentioning
confidence: 99%